Compressive stress inhibits proliferation in AsPC-1 pancreatic cancer cells and reduction of Myc protein - Fuko Miyake; Seiichiro Ishihara; Naomi Ando; Shoichiro Tange; Atsushi Enomoto; Hisashi Haga (PLoS ONE, 2026)
Cancer cells grow in confined tumor microenvironments and push the surrounding tissue, which reacts and exposes them to compressive stress. Previous studies have revealed that compressive stress inhibits proliferation in breast and colorectal cancer cells. It has been reported that pancreatic tumors accumulate compressive stress in vivo , but it is not well understood whether compressive stress regulates proliferation in pancreatic cancer cells. Therefore, the effect of compressive stress on the proliferation of human pancreatic cancer cells was investigated in this study. We found that the growth of compressed AsPC-1 human pancreatic cancer cells was slower than that of uncompressed cells. Furthermore, the protein expression of Myc was reduced in compressed cells, which inhibited their proliferation. In addition, the expression of Snail, which is correlated with poor prognosis in pancreatic cancer patients, was promoted by compressive stress and the inhibition of Myc. These results suggest that compressive stress inhibits proliferation and triggers Snail expression via the reduction of Myc protein in AsPC-1 pancreatic cancer cells.